A computational study of the effect of geomagnetic activity on the planetary circulation of the Earths atmosphere - Mingalev, I. V.; G. Orlov, K.; Mingalev, V. S. (JOURNAL OF ADVANCES IN PHYSICS, 2016)
The effect of geomagnetic activity on the global circulation in the Earths atmosphere is studied with the help of the non-hydrostatic mathematical model, developed earlier in the Polar Geophysical Institute. The mathematical model allows us to calculate three-dimensional global distributions of the zonal, meridional, and vertical components of the wind velocity and neutral gas density in the layer surrounding the Earth globally and stretching from the ground up to the altitude of 126 km. Simulations were performed for the summer period in the northern hemisphere (16 July) and for three distinct values of geomagnetic activity (Kp=1, 4 and 7). The simulation results indicated that the effect of geomagnetic activity on the global neutral wind system may be essential not only above 80 km but also below this altitude (in the mesosphere, stratosphere and troposphere). A physical mechanism, responsible for the influence of geomagnetic activity on the global neutral wind system in the mesosphere, stratosphere and troposphere, has been established with the help of the model calculations.